Worker Reciprocity and the Returns to Training: Evidence from a Field Experiment - Jan Sauermann (Institute for the Study of Labor (IZA), 2015)
Workers' reciprocal behavior is one argument used to explain why firms invest in employee human capital. We explore the relation between firm-sponsored training and reciprocity by providing evidence that workers reciprocate employer training investments by making greater effort. Using a field experiment with random assignment to a training program, we show that reciprocal workers have significantly higher performance than their non-reciprocal peers after participation in the training course. This result suggests that reciprocal workers exert greater effort in response to the firm's investment.
Keywords: J24; M53; D01; 330; firm-sponsored training; reciprocity; field experiment